Evaluating the Effectiveness of I-Zoo Interactive Learning for Students with Special Educational Needs (Hearing Impairment) - Abdul Rahman, Nur'Hamizah; Gnana Piragasam, Grace Annamal (Journal of Research, Innovation, and Strategies for Education (RISE), 2024)
Recent advancements in educational technology have demonstrated potential in supporting the unique learning needs of Special Educational Needs (SEN) students. However, there are challenges regarding how the integration of this technology can provide the same benefits to all students within this diverse group, particularly in special education. In today's educational landscape, the integration of technology-supported tools and resources for SEN students is becoming increasingly important, although their effectiveness can vary significantly depending on individual needs and learning contexts. The objective of this study is to assess the effectiveness of the interactive learning platform I-Zoo on the cognitive abilities of SEN students with hearing impairments, focusing specifically on recognition, signalling, and spelling skills. The study methodology adopts an action research approach, involving a pre- and post-intervention design to evaluate the impact of I-Zoo on cognitive skills and employs descriptive analysis. The study's findings show a significant increase in scores, with a 44% improvement observed after the intervention. This suggests that interactive learning tools like I-Zoo have the potential to enhance specific cognitive abilities among SEN students. However, the varying levels of improvement highlight the need for further adaptation and customisation of these tools to better meet individual learning needs. Further research is needed to explore the long-term effects of this technology and its integration into broader learning frameworks to maximise its benefits for all SEN students.
Keywords: Special Educational Needs (SEN); Technology-supported Equipment and Materials; Hearing-impaired; Interactive Learning; Cognitive abilities